Population Biology of the Indian River Shad, Gudusia chapra (Clupeidae) in the Old Brahmaputra River, North-Eastern Bangladesh - Ferdous Ahamed; Zoarder Faruque Ahmed; Md. Yeamin Hossain; Jun Ohtomi (Universiti Kebangsaan Malaysia, 2014)
Population biology including population structure, reproduction, length-weight relationship and condition factor of a commercially important clupeid freshwater fish, Gudusia chapra was studied in the Old Brahmaputra River, Bangladesh during January-December 2009. In the present study, a total of 2032 specimens (1091 male; 941 female) were collected. The overall sex ratio showed significant difference from the expected value 1:1 (male: female = 1:0.86, χ2 = 11.07, p<0.001). Length-frequency distribution showed a size predominance of females over males, where mean female size consistently exceeded that of males throughout the year. Female size at first sexual maturity was estimated as 8.3 cm in standard length (SL). Monthly gonadosomatic index (GSI) was higher during March-September with a peak in April, indicating this was the main spawning season. The allometric coefficient b of the length-weight relationship (LWR) indicated negative allometric growth in males and females, but the analysis of covariance (ANCOVA) showed significant differences in slope and intercept between the sexes (p<0.001). Fulton’s condition factor by months and SLs varied in both sexes and was attributed to variations in GSI with maturity.